Lixiviação, formação de resíduos ligados e biorremediação de atrazina em solo subtropical submetido à aplicação de água residuária da suinocultura - Gonçalves, Morgana Suszek (2010)
Atrazine is a triazine herbicide, widely used in agriculture to control weeds in corn and cane sugar farming. However, atrazine is considered a pesticide moderately persistent in the environment and the application of wastewater to the soil can affect its environmental performance. In this study, the effects of wastewater from swine (ARS) in leaching, dissipation, and bound residue formation of atrazine in a subtropical clay soil were evaluated. Also, this work was carried out to isolate and identify micro-organisms present in the ARS, resistant to atrazine and possible use in bioremediation of contaminated soils. For the leaching test soil columns filled with samples of a distroferric Red Latossol were used, which received the application of atrazine at a dose of 5 L ha-1, and were incubated for 7 days according to the following treatments: T1 (Sterile soil + ARS), T2 (Sterile soil + distilled water), T3 (Non sterile soil + ARS) and T4 (Non sterile soil + distilled water). In T1 and T3 the amount of ARS was applied corresponding to five times the recommended dose of nitrogen for the corn crop. To study the formation and dissipation of atrazine bound residues, we conducted experiments in the laboratory under controlled conditions, where samples of the same Latossol received the application of 168.61 mg kg-1 of atrazine and incubated for 60 days according with the same treatments considered in the leaching tests. The extractable residues of atrazine and bound residues were extracted and analyzed by high performance liquid chromatography. The isolation and identification of micro-organisms, they were cultivated under controlled conditions in liquid medium containing 0.01 and 0.1 g L-1 atrazine and peaked on solid medium containing 10 mg L-1 for atrazine, for observation of growth. The results showed that the application of ARS to the ground, above the agronomically recommended dosage, the higher the leaching of atrazine in the soil profile, and consequently the risk of contamination of groundwater. There was no effect of wastewater from swine in the dissipation of atrazine. However, the addition of ARS the soil favored the increased formation of bound residues, which can increase the persistence of atrazine in the environment and reduce its bioavailability. We isolated three bacteria of the genus Corynebacterium spp and three fungi of the species Cladosporium cladosporioide, Rhizopus stolonifer and Penicillium purpurogenum present in the ARS and herbicide resistance. The growth of bacteria and fungi in medium supplemented with atrazine indicated the possibility of using these micro-organisms in the bioremediation of soils contaminated with atrazine.